2016
DOI: 10.4102/sajesbm.v8i1.45
|View full text |Cite
|
Sign up to set email alerts
|

Internships enhancing entrepreneurial intent and self-efficacy: Investigating tertiary-level entrepreneurship education programmes

Abstract: <p><strong>Background:</strong> Entrepreneurship education interventions are deemed effective when they enhance interns’ entrepreneurial intent (EI) and entrepreneurial self-efficacy (ESE). Notwithstanding the emergence of internship as an experiential learning approach in entrepreneurship education, evidence about their potential to foster EI and ESE lacks systemisation.</p><p><strong>Aim:</strong> The aim of this study was to determine whether internships enhance EI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 57 publications
2
26
0
2
Order By: Relevance
“…The positive relationship found between entrepreneurial internship program and entrepreneurial self-employment among university students indicates that the availability of an entrepreneurial internship program will lead to the entrepreneurial self-employment among the students. The findings are in line with previous studies that found similar results (Botha & Bignotti, 2016;Chou et al, 2017;Nurhuda & Soenarto, 2018;Zreen et al, 2019). Therefore, universities aimed at designing entrepreneurial development programs should emphasize the entrepreneurial internship program as an intervention to produce entrepreneurs among the graduates.…”
Section: Structural Modelsupporting
confidence: 92%
See 1 more Smart Citation
“…The positive relationship found between entrepreneurial internship program and entrepreneurial self-employment among university students indicates that the availability of an entrepreneurial internship program will lead to the entrepreneurial self-employment among the students. The findings are in line with previous studies that found similar results (Botha & Bignotti, 2016;Chou et al, 2017;Nurhuda & Soenarto, 2018;Zreen et al, 2019). Therefore, universities aimed at designing entrepreneurial development programs should emphasize the entrepreneurial internship program as an intervention to produce entrepreneurs among the graduates.…”
Section: Structural Modelsupporting
confidence: 92%
“…Internships refer to on the job training programs, which provide students with field knowledge related to their study in a supervised learning environment (Botha & Bignotti, 2016;Chou et al, 2017). The main objective of the internship program is to reinforce the knowledge learned in the classroom by providing an avenue for students to apply the knowledge in the real-world (Fitzgerald et al, 2014).…”
Section: Entrepreneurial Internship Programmentioning
confidence: 99%
“…The influence of local industry and regional knowledge production and transfer on propelling entrepreneurial activities is undeniable (Wynn and Jones, 2018). Botha and Bignotti (2016) make the point that in seeking to inculcate an entrepreneurial culture education has a double purpose: shaping minds as well as developing necessary knowledge and skills. Learning is also heavily influenced by the frame of reference, stemming from earlier life experiences, that shapes the learners’ values, beliefs and assumptions about themselves and the world in which they live (Guthrie, 2011).…”
Section: Action Learning and Youth Ese Developmentmentioning
confidence: 99%
“…In practical activities students are trained to work real before they graduate. Work experience gained during the internship can affect students' interest in entrepreneurship (Farouk A., et al, 2014;Hasbi, 2017;Botha, M. et al, 2016). Hurst, Jessica L., et al (2014) also said that internship activities are key in career preparation, professional development and career improvement for students.…”
Section: Introductionmentioning
confidence: 99%